Inflammatory Response Markers as Predictors of Colorectal Cancer Prognosis - Minsung Kim; Il Tae Son; Bo Young Oh (The Ewha Medical Journal)
Colorectal cancer (CRC) is a globally prevalent and challenging malignancy. Accurate prognosis prediction is essential for optimizing patient care. This comprehensive review discusses the intricate relationships between inflammatory response markers and CRC prognosis. Inflammatory response markers have gained prominence as a prognostic tool. Elevations in the preoperative neutrophil-lymphocyte ratio, platelet-lymphocyte ratio, and C-reactive protein-albumin ratio predict a poor prognosis for patients with CRC. A decreased lymphocyte-monocyte ratio is also a poor prognostic factor. A high Glasgow prognostic score and a high modified Glasgow prognostic score are associated with adverse outcomes, including reduced survival. While significant progress has been made, challenges remain in standardizing the clinical application of these inflammatory response markers. Prospective research and further investigations are warranted to refine the prognostic models. Enhanced understanding and utilization of these inflammatory response markers will help advance personalized treatment strategies, refine surveillance protocols, and improve the management of CRC.